Implication of Constructivism Philosophy on Teacher Professional Development: A Literature Review - Affandi, Lalu Hamdian; Tantra, Dewa Komang (FKIP Universitas Lampung, 2022)
Background: Constructivism is a popular term in the field of student learning but not in the field of teacher professional development. Objectives: Aim of current study is exploring implication of constructivism on teacher professional development. Methods: This is a literature review conducted by selecting, evaluating, and synthesizing findings from previous research. Information found are analyzed by employing thematic approach. Findings: Constructivism views learning as active processes through which human grow by developing effective behavior in creating suitable adaptation to their environment. Implications of constructivism views on teacher professional development are growth is the ultimate purpose of teacher professional development, problem-based professional development, evaluation-integrated professional development, and ongoing professional development through learning by doing. Conclusion: Those implications can be seen as general principles in creating effective professional learning for teachers. The principles need to be investigated further in order to assess its efficacy against teachers working conditions. Keywords: constructivism, teacher professional development, teacher professional learning.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202232